2021
DOI: 10.1016/j.jcmgh.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Findings of Hepatic Severe Acute Respiratory Syndrome Coronavirus-2 Infection

Abstract: Background and Aims Liver injury due to COVID-19 is being increasingly recognized. Abnormal liver chemistry tests of varying severities occur in a majority of patients. However, there is a dearth of accompanying liver histologic studies in these patients. Methods: The current report details the clinical courses of two patients having severe COVID-19 hepatitis. Liver biopsies were analyzed under light microscopy, portions of liver tissue were hybridized with a target probe to the SARS-CoV-2 S gene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 32 publications
0
73
1
2
Order By: Relevance
“…Liver histology in other COVID-19 cases presented a mixed inflammatory infiltration with marked bile duct damage, features of endotheliitis and many apoptotic bodies. The intrahepatic presence of SARS-CoV-2 was even suggested in electron microscopy and in-situ hybridization, indicating the possibility of direct cell injury[ 93 ]. The ultrastructural assessment of postpartum liver tissue biopsies derived from two deceased COVID-19 patients by Wang et al [ 94 ] revealed typical coronavirus particles with their spikes in the cytoplasm of hepatocytes.…”
Section: Histological Appearance Of the Liver During The Course Of Comentioning
confidence: 99%
“…Liver histology in other COVID-19 cases presented a mixed inflammatory infiltration with marked bile duct damage, features of endotheliitis and many apoptotic bodies. The intrahepatic presence of SARS-CoV-2 was even suggested in electron microscopy and in-situ hybridization, indicating the possibility of direct cell injury[ 93 ]. The ultrastructural assessment of postpartum liver tissue biopsies derived from two deceased COVID-19 patients by Wang et al [ 94 ] revealed typical coronavirus particles with their spikes in the cytoplasm of hepatocytes.…”
Section: Histological Appearance Of the Liver During The Course Of Comentioning
confidence: 99%
“…While concomitant liver injury has been commonly observed among patients with severe COVID-19 pneumonia 3,4 , clinical presentation of COVID-19 with hepatitis as the predominant feature has been rarely reported [5][6][7] . All these cases had positive PCR for SARS-CoV-2 in nasopharyngeal swabs at admission, three had concomitant pulmonary involvement and two had predisposing liver conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Liver injury with mild or moderate elevation of transaminases has been observed in about half of patients requiring hospital admission for severe COVID-19 3,4 . However, acute febrile hepatitis as a predominant manifestation of COVID-19 has been rarely reported and has been mainly observed among patients with underlying liver diseases and/or concomitant signs of upper or lower respiratory tract involvement with diagnosis established by polymerase chain reaction (PCR) in nasopharyngeal swabs [5][6][7] . We report here a case of a young previously healthy man presenting with febrile hepatitis as a unique clinical manifestation, for which diagnosis of COVID-19 was established by seroconversion.…”
Section: Introductionmentioning
confidence: 99%
“…Death may occur long after the acute liver injury is noted; subsequently, histological changes may have been eliminated or obscured, and viral load would have diminished over time. Fiel et al [ 18 ] presented their findings from two liver biopsies performed on patients infected with SARS-CoV-2. Both patients had severe hepatic failure in the absence of obvious involvement of other organs.…”
Section: Clinical Features Of Hepatic Injury In Covid-19mentioning
confidence: 99%